Peran Perempuan dalam Perekonomian Keluarga Petani di Pantura Kecamatan Brondong Kabupaten Lamongan - Nikmah, Nafidatun; Muhammad Khowiludin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Many women from the north coast of Lamongan work in the vegetable trading sector because this sector is able to provide a regular source of income. Apart from that, the vegetable farming sector also provides enormous opportunities for the involvement of women because the jobs that work in the circulation of vegetable farmers are very young. This research focuses on the role of women in their work that runs in the agricultural sector and whether the role they build can make a bargaining position in family decision-making. This research was conducted at a vegetable market located in Sendangharjo Village, Pambon and Sedayu, Lamongan. In this study used a descriptive qualitative approach, the data obtained using the method of observation, interviews, and documentation. Furthermore, the data was analyzed through several stages starting with data collection, data reduction, data presentation and drawing conclusions. Then triangulation of data was carried out to test the validity of the data. The results of the study show that the role of women fish traders who have an incomprehensible sense of why they have to work is very influential in improving the family's economy. At the level of access and control, women have made progress, even though men tend to be in a superior position. For those same people, they have been mutually dependent and supported in their roles between husband and wife